(untitled) (Fiep Bulletin - online, 2013)
Type 1diabetes mellitus (T1DM) is a chronic disease characterized by the autoimmune destruction of insulinproducing beta cells of the pancreatic islet of Langerhans. Their destruction leads to complete insulin deficiency. The autoimmune reaction in T1DM is caused by an association of environmental and genetic factors. Uncontrolled glucose levels and diabetes may lead to blindness, damage to the nervous system, cardiovascular diseases and other complications. Physical exercises are associated with the reduction of cardiovascular mortality in patients with T1DM, and there seems to be an important association between physical exercise and glucose control in patients with T1DM.